Membangun Organizational Citizenship Behavior pada Karyawan Perbankan Syariah di Indonesia - Gunarto, Muji; Harahap, Dedy Ansari; Purwanto, Purwanto; Amanah, Dita; Umam, Khoirul (Jurnal Manajemen, 2020)
The development of Islamic Commercial Banks (ICB) in Indonesia is quite rapid, but the performance of Islamic banks is not optimal when compared to conventional banks. One of the advantages of Islamic banks is that employees have the same faith, so that Islamic values play an important role in organizational life. The purpose of this study was to determine whether the Organizational Citizenship Behavior (OCB) can be implemented and how to build OCB in Islamic banking so as to improve organizational performance. The survey was conducted on 300 employees of Islamic banking in Indonesia (Medan, Palembang, Jakarta, Bandung and Surabaya). The sampling technique was carried out by proportional random sampling. The data analysis technique was carried out by using the structural equation modeling (SEM) approach with the LISREL program application. The results of the analysis show that Islamic work ethic, Islamic personality and competence are the determining factors for building OCB for employees in Islamic banking. Employees who show work enthusiasm, hard work, sincere work, gratefulness, commitment and professionalism will produce quality, participatory performance, desire and have the ability to help, respect and maintain the organization. Employees with Islamic personalities, having a strong and humble belief will be better at work and care for their colleagues, leaders and also the organization. The willingness and willingness of employees in conveying ideas, sharing knowledge, giving mutual advice and tausyiah can increase employee gratitude, cooperation, sincerity and trust so that the OCB of employees at Islamic banks is increasing.